Diagnosing Pediatric Patients With Hereditary C1-Inhibitor Deficiency—Experience From the Hungarian Angioedema Center of Reference and Excellence - Andrási, Noémi; Balla, Zsuzsanna; Visy, Beáta; Szilágyi, Ágnes; Csuka, Dorottya; Varga, Lilian; Farkas, Henriette (Frontiers in Allergy, 2022)
Background: Hereditary Angioedema with C1-inhibitor deficiency (C1-INH-HAE) is a rare disease characterized by recurrent subcutaneous and/or submucosal edematous (HAE) episodes, which may occur at any age. The mean age of symptom onset is 10-12 years. Diagnostic protocols differ by age group and family history. Methods: We retrospectively analyzed clinical and laboratory data (C4-, C1-INH concentration and function) from 49 pediatric patients diagnosed with C1-INH deficiency at our Angioedema Center between 2001 and 2020. Moreover, we analyzed the connection between complement parameters and symptom onset. Results: From the 49 pediatric patients (boy/girl: 23/26, average age of diagnosis: 6.7 years min: 0-max.: 18.84) the majority (36/49, 73%) was diagnosed as the result of family screening. From all the enrolled patients, 34% (17/49) experienced symptoms before the diagnosis. During the observational period 33% (16/49) of the patients remained asymptomatic, while 33% (16/49) became symptomatic. The average age at symptom onset was 7.8 years (min.: 0.5 – max.: 18). Only 27% (13/49) of pediatric patients were diagnosed after referrals to our Center because of typical symptoms. From those patients diagnosed with family screening, 4/36 experienced symptoms at or before the time of the diagnosis. In case of 5 newborns, from the family screening group, umbilical cord blood samples were used for complement testing. In case of 3/36 patients first complement parameters did not clearly support the disease, but the presence of the mutation identified in the family verified the diagnosis. Complement results were available from 11 patients who became symptomatic during the observational period. Complement parameters 1 year prior to and after the onset of symptoms were compared and significantly lower concentrations of C1-INH (p=0.0078) were detected after the onset of symptoms compared to the preceding (symptom-free) period. Discussion: The majority of pediatric patients were diagnosed as a result of family screening before the onset of symptoms. Early diagnosis allows to supply the patients with special acute treatment for HAE attacks, which may occur at any time. Our results highlight the importance of DNA analysis in pediatric patients in case of known mutation in the family, and ambiguous result of complement testing.